ANALISIS UPAYA PEMERINTAH DAERAH KABUPATEN PAMEKASAN DALAM MENDUKUNG BISNIS JAMU MADURA DI KABUPATEN PAMEKASAN (Analysis Of the Pamekasan Regional Governments' Effort in Supporting the Jamu Madura Business in The Pamekasan Regency) (Agridevina : Berkala Ilmiah Agribisnis, 2022)
Jamu is one of the typical Indonesian drinks that has existed for a long time and continues to exist today. Madura is one of the regions in Indonesia that produces a great deal of herbal medicine that is beneficial to the body, so several entrepreneurs have increased their international market share. For some Madurese, particularly women, the herbal medicine business is their primary source of income. Over time, the development of drugs is getting faster and more effective in curing diseases. It causes the traditional Madurese herbal agro-industry to decline and impacts the economy of Madura herbal medicine entrepreneurs. This study aims to analyze the efforts of the Pamekasan district government in supporting the Madurese herbal medicine business in the Pamekasan district with qualitative descriptive research methods. This study shows that the Pamekasan district government has conducted several programs to develop the traditional herbal medicine agro-industry in the Pamekasan district quite well. However, it still does not reach all herbal producers in the area, such as the less well-known Madura herbal medicine producers. DOI : https://doi.org/10.33005/agridevina.v11i2.3473